Body-Focused Spirituality: The Impact of Spatial Structural Changes on Religious Experience - Bognár, Bulcsu (Journal for the study of religions and ideologies, 2025)
Drawing on insights from the spatial turn, this analysis examines the role of spirituality in religious experience, particularly focusing on how the body becomes central to transcendent experience in relation to spatial structural changes. It investigates how the emergence of hybrid social spaces contributes to the decline of institutionalised religiosity and how new forms of religiosity amplify the role of individual meaning-making. The paper focuses on how changes in the spatial structure of religious spaces are transforming the perception of the body among religious persons and how body-centred spiritualism is becoming central to religious experience. In this context, the paper discusses both the secular sources of spiritual bodily experience and the new features of sacred experience associated with the changed spatial structure. The analysis interprets this complex phenomenon in terms of body-focused spiritualism. The theoretical novelty of the analysis lies in the fact that, while interpreting spirituality and embodied transcendental experience, it not only relies on classical authors of spatial theory, but also draws on insights from phenomenological analysis in its interpretation of social spaces, the conceptual (spatial) domains of reality, and the body.